Can we estimate late-onset sepsis by serial methemoglobin levels? An observational study in preterm neonates - ÖZEK, EREN (My University, 2023)
Objective: To assess serial methemoglobin (MetHb) levels in preterm infants as a possible diagnostic method for late-onset sepsis (LOS). Methods: Preterm infants were assigned into two groups: those with culture-proven LOS and controls. Serial MetHb levels were measured. Results: The MetHb values of the LOS group were found to be significantly increased (p 1.75%, optimized for a sensitivity of 81.9% and specificity of 90%. After antimicrobial therapy, MetHb values were found to decrease significantly (p 2% (p 2% is associated with LOS mortality.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Cerrahi Tıp Bilimleri; Patoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Internal Medicine Sciences; Child Health and Diseases; Surgery Medicine Sciences; Pathology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; PEDİATRİ; PATOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; PEDIATRICS; PATHOLOGY; Pediatri, Perinatoloji ve Çocuk Sağlığı; Patoloji ve Adli Tıp; Pediatrics, Perinatology and Child Health; Pathology and Forensic Medicine; Biomarker; late-onset sepsis; methemoglobin; neonate; preterm infants